Experiences and opinions of non-medical prescribers in a paediatric hospital concerning electronic prescribing. Issue 6 (9th May 2013) - Burridge, A; Terry, D
Abstract : Aims: To evaluate resources used by non-medical prescribers (NMPs) whilst making prescribing decisions. Describe any difficulties concerning the availability of paediatric prescribing information to NMPs required for writing prescriptions. Establish views of NMPs on the benefits and concerns about a move to electronic prescribing (ePrescribing). Method: Two focus groups held (17 participants) onsite with NMPs from a variety of specialties with a range of prescribing experience. Participants followed a pre-set focus group guide with occasional direction from the facilitator. Text was transcribed and coded using NVivo software (V.9). Results: The reference source most frequently referred to was the BNFc. NMPs also refer to colleagues, local guidelines and clinic letters regularly. Most difficulties with prescribing refer to a lack of access to information about previous prescriptions and notes being unavailable. Participants agreed that ePrescribing should provide dosing support through calculations based on patient weight/BSA/age. Guidance on monitoring and access to historic prescriptions were also desirable. Alerts (eg, regarding allergies, monitoring or interactions) should require some form of acknowledgement, but participants expressed some concern about alert fatigue occurring. Concerns about ePrescribing implementation mainly referred to IT related problems due to the difficulties being experienced with the current systems. Further issues were raised about the availability of computers if all prescribing was electronic. Security of passwords and being able to trace editing of your prescribing also caused reservations. After IT related issues, the next most frequent concern was having a suitable lead in time to ensure all staff were comfortable with using the new system. Participants could describe many perceived benefits of a move to a successful ePrescribing system. Benefits stated include: always being able to access patient's medication history (n=5); better audit trail of prescriptions (eg, changes could be tracked) (n=5); easier monitoring of medicines and administration of medicines (n=5); guidance on dosing available and individualised to your patient (n=4); reduced waiting times for discharge medication (n=3); access to a local formulary that lists available unlicensed products (n=2).;less transcription errors (n=1); reduced delays in administration of medicines as charts would not be held in pharmacy (n=1) and no lost prescriptions (n=1). Conclusions: NMPs currently use a wide range of resources to support their prescribing decisions. There are some difficulties accessing paediatric information for certain specialties (eg, palliative care and renal) and patients' prescribing histories. NMPs can see a range of benefits to moving to electronic prescribing, but there is a lack of optimism about its potential success due to the current technical difficulties experienced in the Trust's IT systems.